The risk of fracture to the tibia from a fragment simulating projectile. (February 2020) - Nguyen, Thuy-Tien N.; Carpanen, Diagarajen; Stinner, Daniel; Rankin, Iain A.; Ramasamy, Arul; Breeze, Johno; Proud, William G.; Clasper, Jonathan C.; Masouros, Spyros D.
Abstract: Penetrating injuries due to fragments energised by an explosive event are life threatening and are associated with poor clinical and functional outcomes. The tibia is the long bone most affected in survivors of explosive events, yet the risk of penetrating injury to it has not been quantified. In this study, an injury-risk assessment of penetrating injury to the tibia was conducted using a gas-gun system with a 0.78-g cylindrical fragment simulating projectile. An ovine tibia model was used to generate the injury-risk curves and human cadaveric tests were conducted to validate and scale the results of the ovine model. The impact velocity at 50% risk (±95% confidence intervals) for EF1+, EF2+, EF3+, and EF4+ fractures to the human tibia – using the modified Winquist-Hansen classification – was 271 ± 30, 363 ± 46, 459 ± 102, and 936 ± 182 m/s, respectively. The scaling factor for the impact velocity from cadaveric ovine to human was 2.5. These findings define the protection thresholds to improve the injury outcomes for fragment penetrating injury to the tibia.